Influence of Single-Phase Solar Photovoltaic Systems on Total Harmonic Distortion: A Case Study - Chin Kim Gan; Sara Ragab Mahmoud; Kyairul Azmi Baharin; Mohd Hendra Hairi (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
The installation of small-scale solar photovoltaic system has recently gaining popularity in Malaysia mainly driven by the Feed-in Tariff scheme. Given its relatively small generation capacity, the single-phase solar inverters are not required to comply with power quality standard. Neverthelss, the impact of small-scale solar system on the grid could become significant when the penetration is increasing over the years. In this regard, this paper presents a case study on the influence of single-phase grid-connected solar photovoltaic systems on the total harmonic distortion for current at the point of common coupling. Field measurements have been carried out for a total of 12 single-phase solar systems which were installed at three different locations at Universiti Teknikal Malaysia Melaka. Detailed analyses have been performed to characterize the aggregated current harmonic performance for the overall system.  The findings from the presented case study suggest that the current quality from the inverter is highly dependent on the level of inverter output. Hence, the proper selection of the array-to-inverter ratio at the system design stage could greatly improve the overall total harmonic performance performance for current.The installation of small-scale solar photovoltaic system has recently gaining popularity in Malaysia mainly driven by the Feed-in Tariff scheme. Given its relatively small generation capacity, the single-phase solar inverters are not required to comply with power quality standard. Neverthelss, the impact of small-scale solar system on the grid could become significant when the penetration is increasing over the years. In this regard, this paper presents a case study on the influence of single-phase grid-connected solar photovoltaic systems on the total harmonic distortion for current at the point of common coupling. Field measurements have been carried out for a total of 12 single-phase solar systems which were installed at three different locations at Universiti Teknikal Malaysia Melaka. Detailed analyses have been performed to characterize the aggregated current harmonic performance for the overall system.  The findings from the presented case study suggest that the current quality from the inverter is highly dependent on the level of inverter output. Hence, the proper selection of the array-to-inverter ratio at the system design stage could greatly improve the overall total harmonic performance performance for current.